Note on the effect of low temperatures on the survival of immature stages of the rusty grain beetle, Cryptolestes ferrugineus - Barker, P.S. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Wheat infested with the rusty grain beetle (Cryptolestes ferrugineus) was held for varying numbers of weeks at temperatures of -5°, 0°, 5°, 10°, and 15°C in separate tests. Survival of the immature stages (eggs, larvae and pupae) of the beetle declined each week at each temperature. The LT50 and LT99 were determined for each of the temperatures except for -5°C where 100 % mortality was observed in a 1- to 2-week period of exposure.